2020
DOI: 10.1155/2020/7890305
|View full text |Cite
|
Sign up to set email alerts
|

Pantoea agglomerans Bacteremia: Is It Dangerous?

Abstract: Introduction. Pantoea agglomerans, an anaerobic Gram-negative bacillus, is a rare cause of opportunistic infections affecting premature infants to seniors. We present a 34-year-old man who was presented for the management of diabetic ketoacidosis and developed Pantoea agglomerans bacteremia after one week of hospitalization. Case Presentation. A 34-year-old African-American male with uncontrolled diabetes mellitus type I and recurrent skin infections was admitted with diabetic ketoacidosis. He had left upper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Interest ngly, there was a case of per ton t s due to contam nated d alys s solut on n 2 years old female pat ent 1,8,9 . Case reports of bacter em a due to IV u ds contam nated w th P. agglomerans are qu te h gher n number than other nfect ons 5 . It s mport to ment on that Pantoea agglomerans s a member of Enterobacterales and res dent of normal gastro ntest nal ora of human.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interest ngly, there was a case of per ton t s due to contam nated d alys s solut on n 2 years old female pat ent 1,8,9 . Case reports of bacter em a due to IV u ds contam nated w th P. agglomerans are qu te h gher n number than other nfect ons 5 . It s mport to ment on that Pantoea agglomerans s a member of Enterobacterales and res dent of normal gastro ntest nal ora of human.…”
Section: Discussionmentioning
confidence: 97%
“…In certa n cases, P. agglomerans can cause wound nfect ons, so t ssue or jo nt nfect ons by penetrat ng plant mater als conta n ng the bacter um. 1,5 Although rare, nosocom al nfect ons due to P. agglomerans are also reported such as bacter em a, pneumon a, sept c arthr t s, ur nary tract nfect ons, per ton t s, surg cal wound nfect ons and catheter related nfect ons espec ally n mmunocomprom sed pat ents a ect ng all age groups nclud ng premature and elderly. 5,6 It s worth ment on ng that P. agglomerans surv ve at very low temperatures such as +4 O C and can cause bacter em a by contam nat on of ntravenous u ds, total parenteral nutr t on, the anesthet c agents, and blood products 5 Bes de ts pathogen c ty, some recent stud es showed that sc ent st can benef t some propert es of P. agglomerans l ke ant b ot c product on and mmunopotent ator e ect to prevent or treat nfect on d seases both n humans and an mals.…”
Section: Introductionmentioning
confidence: 99%
“…This is a yellow Gram-negative rod, commensal and opportunistic human pathogen. 107 It is found in water, soil, sewage, vegetables, seeds, feces and foodstuffs. Telias et al 108 found Enterobacter to be abundant on the surface of tomatoes.…”
Section: Pantoea (Enterobacter) Aglomeransmentioning
confidence: 99%
“…Dutkiewicz et al 113 reviewed cases of Pantoea infections linked to trauma from plant material. The case of an infected diabetic male was presented by Kaur et al 107…”
Section: Pantoea (Enterobacter) Aglomeransmentioning
confidence: 99%
“…The genus Pantoea, gram-negative rods with yellow pigmentation belonging to the Erwiniaceae family, has been reported to cause opportunistic infections in immunocompromised patients. Only a few cases of spontaneous Pantoea agglomerans bacteremia have been reported, mostly among pediatric, hospitalized, immunocompromised, or cancer patients [1][2][3]. Although it is present in the soil, plant surfaces, human excreta, vegetables, and fruits, it is known to jump kingdoms and cause a clinical spectrum of diseases ranging from diarrhea, sepsis, arthritis, osteomyelitis, synovitis, urinary tract infections, pneumonia, to septic shock in humans [3][4][5].…”
Section: Introductionmentioning
confidence: 99%